Characterization of Bacterial Strains and Their Resistance Status in the Hospital Environment: Systematic Review - Diego Alejandro ESTRADA RIOS; Isabela MUÑOZ ARIAS; Alvaro Javier CASTELLANOS GARCÍA; Monica CHAVEZ VIVAS (Modern Medicine)
Background: Clinical environments are considered reservoirs of antibiotic-resistant microorganisms that lead to the constant progression of nosocomial infections. The objective of this systematic review is to provide an epidemiological description of the role of the hospital environment as a reservoir of antibiotic-resistant bacteria and antibiotic-resistance genes. Materials and Method: A systematic review based on the PRISMA guide was carried out, from the Science Direct, Redalyc, Scopus, Hinari, Scielo, Dialnet, PLOS, ProQuest, Taylor, Lilacs and PubMed databases with original studies conducted between January 2013-July 2024. Results: A total of 1751 studies were identified, but only 60 studies were considered eligible for inclusión. The most common hospital environment sample sources were inanimate surfaces and medical devices and implements. extended-spectrum β-lactamases-producing Enterobacteriaceae, Methicillin-resistant Staphylococcus aureus and carbapenemase-producing non-fermenting bacilli as the main organisms found in the hospital environment mediated mainly by bla genes. Multidrug-resistant organisms were identified as the most abundant type in most samples, largely due to the ubiquity of efflux pumps (acr, mex, mdt and emr). Conclusion: Our systematic review reveals the hospital environment is an ecological niche with predominance of few clones with a high degree of multi-resistance to antibiotics that contributes to generate new clones that spread through inanimate surfaces and equipment.